Natural Deficiency or Social Oppression? The Capabilities Approach to Justice for People with Disabilities - Barclay, Linda (Journal of moral philosophy, 2012)
Theories of distributive justice are often criticised for either excluding people with disabilities from the domain of justice altogether, or casting them as deficient in personal attributes. I argue that the capabilities approach to justice is largely immune to these flaws. It has the conceptual resources to locate most of the causes of disadvantage in the interaction between a person and her environment and in doing so can characterise the disadvantages of disability in a way that avoids the imputation of natural deficiency. However, I also argue that the capabilities approach cannot accommodate some of the stronger claims advanced by some disability scholars. No plausible capabilities approach can guarantee that social change will always be the just or fair remedy for disadvantage, and there is a small number of severe cases of disability where capability shortfalls will be attributed to the person’s ‘deficient’ physical and mental impairments.